The use and benefit of management accounting practices in Libyan oil companies - Abdarahman M. Kalifa; Iwan Triyuwono; Gugus Irianto; Yeney Widya Prihatiningtias (Emerald Publishing Limited, 2020)
The purpose of this study is to describe the use and benefit of TMAPs and CMAPs in Libyan oil companies.The data were collected by distributing 210 mailed questionnaires to senior financial staff, such as financial managers, heads of cost department, financial accountants, department of management accounting employees, managerial accountants and Auditors. IFAC-based model was used in analyzing evolution stages in Libyan management accounting practices.This study finds that Libyan oil companies use CMAPs more than TMAPs, the latter being commonly used in Libyan manufacturing companies. This study also finds that CMAPs are more beneficial than TMAPs.This study provides more understanding of the use and the benefit of TMAPs and CMAPs and fills research gap regarding the matter, as well as provides new findings that can be used for further research regarding the use and benefit of TMAPs and CMAPs for Libyan oil companies.The results contribute to a better understanding concerning the use and benefit of TMAPs and CMAPs in Libyan oil companies.